Child Labor in the State of Amazonas: Invisibility of the Notification System - Nathália França de Oliveira; Emerson Victor Hugo Costa de Sá; Tommaso Lombardi; Regiane da Silva Rabelo (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To describe the characteristics of reported cases of child labor in general and to compare official reported child labor data with data on sexual exploitation and occupational accidents involving children and adolescents between 2017 and 2021. Methods: Descriptive study based on data from the Notifiable Health Conditions Information System about child labor, work accidents and sexual exploitation of children and adolescents aged between 5 and 17 years. Annual disease notification rates were calculated and grouped by mesoregions of the state of Amazonas. Results: From 2017 to 2021, there were 312 reports of situations of child labor, being 46.8% involving children and 53.2% involving adolescents. Of these notifications, 20 corresponded to child labor itself, 141 to child and adolescent sexual exploitation, and 151 to work-related accidents involving children and adolescents. The South and Center regions were the ones that most underreported child sexual exploitation as child labor. The Southwest and South mesoregions, on the other hand, were the ones that most underreported work accidents involving children and adolescents as child labor. Conclusion: Child labor in Amazonas basically stems from sexual exploitation and, even though it is underreported, it is frequent, although uneven between regions. Confronting the problem in the state necessarily involves improving the information system in order to acknowledge the actual dimension of the problem and then define intervention measures and logistics.